The Role Of AI In Strengthening Student Personal Brand Equity In Higher Education: A Narrative Review And Conceptual Framework (International Journal of Environmental Sciences, 2025)
Generative AI has become a vital partner in higher education, prompting critical inquiries about how individuals formulate, express, and convey identity under algorithmic frameworks. This study proposes a conceptual model that investigates how deliberate, iterative collaboration with artificial intelligence (AI) across the creative cycle (from conception to drafting, evaluation, and portfolio creation) influences students' personal brand equity. We hypothesize that the effects of using AI are not direct; instead, they operate through intermediary mechanisms. Media and algorithmic literacy encompassing provenance awareness, bias identification, platform and audience comprehension, and ethical production—constitute essential avenues that enhance learners' capacity to critically interact with AI products. These literacies serve in improving self-perception by enhancing confidence and self-efficacy. We argue that smart learning environments, which include transparency, understandable feedback, reflective prompts, and disclosure standards, influence these processes by enhancing or limiting their effects. We believe that students' ability to generate attraction, achieve differentiation, and gain recognition represents the outcomes of personal brand equity. This study combines AI application, literacy improvement, behavioral self-processes, and surrounding variables into a single framework, improving the discussion on artificial intelligence's role in creating identities within higher education and establishing a research agenda for examining these causal relationships.